Human Brucella melitensis infections in southern Vietnam - Campbell, J.I. (2017)
Brucellosis is a collective term for infections caused by small Gram-negative coccobacilli belonging to genus Brucella. This genus incorporates the well-described animal pathogens Brucella melitensis, Brucella abortus, Brucella ovis, Brucella suis, and Brucella canis, which are associated with disease in goats, cattle, sheep, pigs, and dogs, respectively. Brucella are facultative intracellular pathogens, and are sequestered by monocytes and macrophages, spreading throughout the body to the liver, spleen, lymph nodes, and bone marrow [1]. These pathogens are synonymous with an aggressive disease syndrome in animals causing abortion, stillbirth, and the delivery of weak offspring. The organisms replicate to high concentrations in the affected tissues and are transmitted through contact with the placenta, foetus, foetal fluids, and vaginal discharge. Notably, goats can shed B. melitensis in vaginal discharge for up to 3 months after abortion and organisms can be shed in milk for the lifetime of an infected animal